Physicochemical and Rheology Properties of Ice Cream Prepared from Sunflower Oil and Virgin Coconut Oil - Trivana, Linda; Suyatma, Nugraha Edhi; Huunaefi, Dase; Munarso, S. Joni; Pradhana, Adhitya Yudha; Rindengan, Barlina (International Coconut Community Journal, 2023)
In the last decade, increasing trends towards the consumption of healthier foods have forced processors of high-fat products (ice cream) to shift their formulations to higher proportions of unsaturated or “healthier” fats. Vegetable oils such as sunflower oil and VCO can be used as a substitute for milk fat, milk solids not fat (skim milk powder), sweeteners, stabilizers and emulsifiers, and mineral water in making ice cream. A study was carried out to determine the effects of the use of the ratio of sunflower oil: virgin coconut oil with palm fruit as a stabilizer in the production of ice cream on physicochemical properties (pH, proximate, overrun, viscosity, and melting rate). The use of palm fruit is based on the content of galactomannan in palm fruit. Premium ice cream with five different ratios of SO and VCO (15:0), (10:5), (7.5:7.5), (5:10), (15:0). The ice cream production involves mixing, pasteurization, homogenization, aging, and freezing. The physicochemical result shows ice cream sample with a ratio SO:VCO (5:10) obtained good physical properties, the lowest first-time drop/ shape retention, and a low melting rate compared to the others. The rheological behavior of ice cream is the non-Newtonian fluids with a pseudoplastic behavior. The apparent viscosity decreased with increasing shear rate.